PRECIS-2 analysis of pragmatic acupuncture trials: a systematic review - Jinwoong Lim; Hyeonhoon Lee; Yong-Suk Kim (BMC, 2024)
Abstract Background Pragmatic acupuncture trials (PATs) are a research tool for assessing the effectiveness of acupuncture treatments in a real-world setting. This study aimed to provide a comprehensive methodological analysis of PATs using the PRECIS-2(PRagmatic Explanatory Continuum Indicator Summary-2) tool to determine their pragmatism. Methods The MEDLINE, EMBASE, Cochrane Central Register for Controlled Trials, CINAHL, Allied and Complementary Medicine Database, China National Knowledge Infrastructure, VIP, WANFANG, Taiwan Periodical Literature Database, KoreaMed, KMbase, Research Information Service System, Oriental Medicine Advanced Searching Integrated System, CiNii and ClinicalTrials.gov were searched. The search included randomised controlled trials (RCTs) and protocols of RCTs that investigated all types of acupuncture and used self-declared pragmatic design. Two authors independently collected the basic information and characteristics of the studies and assessed their pragmatism using the nine PRECIS-2 domains and the additional domain of control. Results A total of 93 studies were included. The means of eligibility, recruitment, organisation, primary outcome, primary analysis, and control domains were statistically larger than three and were shown to be pragmatic. The means of setting, flexibility:delivery, and follow-up domains were not greater than three and were shown to be non-pragmatic. For flexibility:adherence domain was inappropriate for assessment owing to insufficient information in the studies. Conclusions PATs were pragmatic in the domain of eligibility, recruitment, organisation, primary outcome, primary analysis, and control and were not pragmatic in the domain of setting, flexibility:delivery, and follow-up. Future PATs need to strengthen the pragmatism in the setting, flexibility:delivery, and follow-up domains and to describe the flexibility:adherence domain in more detail. Trial registration CRD42021236975.